For a 'semiotic' sociology of literature: reification, ideology and vision of the world between Goldmann and Rossi-Landi (ENTHYMEMA, 2019)
This contribution wants to show how Ferruccio Rossi-Landi’s reflections, some of which are still unpublished and presented in this study for the very first time, enrich Lucien Goldmann’s ones on ideology, reification and vision of the world, thus permitting to understand the possible usage of Rossi-Landian semiotics in a Materialist-Dialectical sociology of literature as Goldmann used to conceive it.
Keywords: semiotics; sociology; literature; reification; ideology